Single-step endoscopic ultrasonography-guided drainage of peripancreatic fluid collections with a single self-expandable metal stent and standard linear echoendoscope - Berzosa, M.; Maheshwari, S.; Patel, K. K.; Shaib, Y. H. (Endoscopy, 2012)
Endoscopic ultrasonography (EUS)-guided drainage of peripancreatic fluid collections (PFCs) is a well described alternative to surgery or percutaneous drainage. However, it is limited by the requirement for a large working channel that allows multiple plastic stent placement, which is only commercially available on therapeutic linear echoendoscopes. Herein, we describe the drainage of PFCs with a single self-expandable metal stent (SEMS) using a single-step technique and standard linear echoendoscope. Seven cases were identified during a retrospective chart review, and included all patients who had undergone EUS-guided drainage of PFCs during a 6-month period. The mean age was 46 years (range 25 – 70 years) and all patients were symptomatic. The mean diameter of PFCs was 8 cm (range 4.1 – 12.5 cm). Previous percutaneous drainage had failed in three patients. A total of 10 PFCs were drained. Three patients had two cysts drained by the same stent and one patient had two separate procedures to drain two distinct cysts. The SEMS was in place for a mean of 13 weeks (range 4 – 34 weeks). Successful placement of SEMS was achieved in all seven cases. Patients were followed for a mean of 18 weeks (range 7 – 35 weeks), and symptom improvement was achieved in all cases. Complete resolution of PFC was achieved in 9 /10 cysts. No complications were encountered. Single-step EUS-guided drainage of PFCs using a single 10-mm SEMS and a standard linear echoendoscope appears to be a feasible endoscopic technique with excellent technical and clinical success rates.